The Sustainability of Sweet Potato Residues from Starch Processing By-Products: Preparation with Lacticaseibacillus rhamnosus and Pediococcus pentosaceus, Characterization, and Application - Lili Zhu; Hongnan Sun; Mengmei Ma; Taihua Mu; Guohua Zhao; Moe Moe Lwin (Foods, 2022)
The effects of Lacticaseibacillus rhamnosus and Pediococcus pentosaceus on the nutritional–functional composition, structure, in vitro saliva–gastrointestinal digestion, and colonic fermentation behaviors of fermented sweet potato residues (FSPR) were investigated. The FSPR was obtained under the condition of a solid-to-liquid ratio of 1/10, inoculation quantity of 1.5%, mixed bacteria ratio 1:1, fermentation time of 48 h, and fermentation temperature of 37 °C. The FSPR showed higher contents of soluble dietary fiber (15.02 g/100 g), total polyphenols content (95.74 mg/100 g), lactic acid (58.01 mg/g), acetic acid (1.66 mg/g), volatile acids (34.26%), and antioxidant activities. As exhibited by FTIR and SEM, the higher peak intensity at 1741 cm−1 and looser structure were observed in FSPR. Further, the FSPR group at colonic fermentation time of 48 h showed higher content of acetic acid (1366.88 µg/mL), propionic acid (40.98 µg/mL), and butyric acid (22.71 µg/mL), which were the metabolites produced by gut microbiota using dietary fiber. Meanwhile, the abundance of Bifidobacterium and Lacticaseibacillus in the FSPR group was also improved. These results indicated that FSPR potentially developed functional foods that contributed to colonic health.